1993
DOI: 10.1103/physrevlett.70.4047
|View full text |Cite
|
Sign up to set email alerts
|

Limits on right-handed charged weak currents from a polarization-asymmetry correlation experiment withIn107

Abstract: A new technique, based on relative measurements of the longitudinal polarization {P) of positrons emitted in two opposite directions with respect to the nuclear polarization {R =P ~/P^), is used to provide constraints on extensions of the standard model (/?o). The first result, i.e., /?//?o =0.926 ±0.041, was obtained with '^'^In. Interpreted in the framework of left-right symmetric models and assuming no mixing, it provides a 90% C.L. lower limit of 225 GeV/c^ for the mass of a possible right-handed charged H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This would then result in a limit on the tensor couplings a factor of about 2 larger than given in Eq. (38). Note that, since the β particle end-point energy is rather large in 8 Li decay (16.1 MeV) the sensitivity to the Fierz term via the factor m/E e is 3.3 times smaller than in 6 He decay.…”
Section: The βν Angular Correlation Amentioning
confidence: 99%
See 1 more Smart Citation
“…This would then result in a limit on the tensor couplings a factor of about 2 larger than given in Eq. (38). Note that, since the β particle end-point energy is rather large in 8 Li decay (16.1 MeV) the sensitivity to the Fierz term via the factor m/E e is 3.3 times smaller than in 6 He decay.…”
Section: The βν Angular Correlation Amentioning
confidence: 99%
“…The measurements were carried out in 107 In [38] and 12 N [39,40]. Since these are relative measurements, the contribution of the Fierz term cancels and the remaining sensitivity to exotic left-handed couplings is strongly suppressed.…”
Section: Limits On Real Scalar and Tensor Couplingsmentioning
confidence: 99%
“…Four such measurements have been performed, with 12 N and 107 In [40][41][42][43][44], all using the already mentioned technique of positronium hyperfine spectroscopy. In these measurements one determined either the ratio R + = P − /P + or R 0 = P − /P 0 , with P −,+,0 the longitudinal polarization for positrons emitted opposite to (P − ) or in the direction of (P + ) the nuclear polarization, or by unpolarized nuclei (P 0 ).…”
Section: Longitudinal Polarization Of β Particlesmentioning
confidence: 99%
“…Presently, the formalism of ß-decay of oriented nuclei is well understood. Very recently, it has been shown that nuclear orientation even provides very advantageous means for the investigation of extensions beyond the Standard Model [6].…”
Section: Beta-asymmetry Measurements With Nuclear Orientationmentioning
confidence: 99%
“…This has been demonstrated very convincingly in the late fifties by the parity violation experiments in ß-decay of polarized nuclei [5], More recently, NO in combination with a positron-polarimeter has been used to provide constraints on extensions of the Standard Model. New limits on right-handed charged weak currents have been established [6].…”
Section: Introductionmentioning
confidence: 99%